Prediction of lithium-ion battery thermal runaway propagation for large scale applications fire hazard quantification - Md Said, Mohamad Syazarudin; Mohd Tohir, Mohd Zahirasri (MDPI, 2019)
The high capacity and voltage properties demonstrated by lithium-ion batteries render them as the preferred energy carrier in portable electronic devices. The application of the lithium-ion batteries which previously circulating and contained around small-scale electronics is now expanding into large scale emerging markets such as electromobility and stationary energy storage. Therefore, the understanding of the risk involved is imperative. Thermal runaway is the most common failure mode of lithium-ion battery which may lead to safety incidents. Transport process of immense amounts of heat released during thermal runaway of lithium-ion battery to neighboring batteries in a module can lead to cascade failure of the whole energy storage system. In this work, a model is developed to predict the propagation of lithium-ion battery in a module for large scale applications. For this purpose, kinetic of material thermal decomposition is combined with heat transfer modelling. The simulation is built based on chemical kinetics at component level of a singular cell and energy balance that accounts for conductive and convective heat transfer.